2017
DOI: 10.1186/s12936-017-2077-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and pregnancy outcomes associated with placental malaria in a prospective cohort of Papua New Guinean women

Abstract: Background Plasmodium falciparum in pregnancy results in substantial poor health outcomes for both mother and child, particularly in young, primigravid mothers who are at greatest risk of placental malaria (PM) infection. Complications of PM include maternal anaemia, low birth weight and preterm delivery, which contribute to maternal and infant morbidity and mortality in coastal Papua New Guinea (PNG).MethodsPlacental biopsies were examined from 1451 pregnant women who were enrolled in a malaria prevention stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(85 citation statements)
references
References 37 publications
(74 reference statements)
4
81
0
Order By: Relevance
“…[5][6][7] Previous studies have shown that primigravidity is a risk factor for placental malaria and resulting obstetric morbidity. 8,9 In a prior analysis of this study cohort, we reported that placental malaria was more likely in women with high malaria burden (defined as ≥2 episodes of symptomatic malaria or ≥50% positive loop-mediated isothermal amplification (LAMP) samples) and was associated with increased rates of preterm birth and a trend towards higher rates of small for gestational age (SGA) neonates. 10 However, little is known about whether the effect of gravidity on placental malaria varies by timing and symptomatology of P. falciparum.…”
Section: Introductionmentioning
confidence: 92%
“…[5][6][7] Previous studies have shown that primigravidity is a risk factor for placental malaria and resulting obstetric morbidity. 8,9 In a prior analysis of this study cohort, we reported that placental malaria was more likely in women with high malaria burden (defined as ≥2 episodes of symptomatic malaria or ≥50% positive loop-mediated isothermal amplification (LAMP) samples) and was associated with increased rates of preterm birth and a trend towards higher rates of small for gestational age (SGA) neonates. 10 However, little is known about whether the effect of gravidity on placental malaria varies by timing and symptomatology of P. falciparum.…”
Section: Introductionmentioning
confidence: 92%
“…25,27 The only community-based study had an even higher MMR estimate, ranging between 600-900 per 100,000 live births in rural settings. 24 Three of the four studies were based on case notes [24][25][26][27] Neonatal health Neonatal mortality rate (NMR) 1 26 Stillbirth rate 8 [24][25][26][28][29][30][31][32] Reproduction Reproductive health Contraception prevalence rate (CPR) 3 [33][34][35] Obstetric and gynaecological admissions owing to abortions 2 36,37 Pregnancy Maternal health Adolescent birth rate 0 n/a STI prevalence in pregnancy 6 25,[38][39][40][41][42] HIV prevalence in pregnancy 7 25,28,32,35,39,41,43 Malaria prevalence in pregnancy 7 27,29,31,32,[44][45][46] Anaemia prevalence in pregnancy 6 25,29,31,32,35,…”
Section: Mortality Indicatorsmentioning
confidence: 99%
“…Previous studies have shown that primigravidity is a risk factor for placental malaria and resulting obstetric morbidity [8,9]. A prior analysis of this study cohort found that placental malaria was more likely in women with high malaria burden (de ned as ≥2 episodes of symptomatic malaria or ≥50% positive loop-mediated isothermal ampli cation (LAMP) samples) and was associated with increased rates of preterm birth and a trend towards higher rates of small for gestational age (SGA) neonates [10].…”
Section: Introductionmentioning
confidence: 85%